2(x+7)=9-2x

Simple and best practice solution for 2(x+7)=9-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+7)=9-2x equation:


Simplifying
2(x + 7) = 9 + -2x

Reorder the terms:
2(7 + x) = 9 + -2x
(7 * 2 + x * 2) = 9 + -2x
(14 + 2x) = 9 + -2x

Solving
14 + 2x = 9 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
14 + 2x + 2x = 9 + -2x + 2x

Combine like terms: 2x + 2x = 4x
14 + 4x = 9 + -2x + 2x

Combine like terms: -2x + 2x = 0
14 + 4x = 9 + 0
14 + 4x = 9

Add '-14' to each side of the equation.
14 + -14 + 4x = 9 + -14

Combine like terms: 14 + -14 = 0
0 + 4x = 9 + -14
4x = 9 + -14

Combine like terms: 9 + -14 = -5
4x = -5

Divide each side by '4'.
x = -1.25

Simplifying
x = -1.25

See similar equations:

| 2(x+3)=4(2x-7) | | 2sin^2x+5sin^2x=3 | | 4x+12n=36 | | Ax+ca=b | | 4x+3(x+2)=13 | | xa+cx=b | | ax+xc=b | | xa+xc=b | | 4y-8=1+5y-36 | | Ax+cx=b | | 2.8=(x/5)^3 | | 43x=4x+18 | | 6x+3=7+4x | | x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 |

Equations solver categories